Fast defect inspection of high-resolution and textured cylindrical lens holder surface using randomized SVD. Issue 1 (2nd January 2017) - Chen, Ssu-Han
Abstract: This paper describes an automatic inspection system for detecting defects on the cylindrical surface of lens holders using machine vision. The system is composed of a charge coupled device, a coaxial light and a motor unit. A sequence of partial surface images of a lens holder is grabbed and is reconstructed into a two-dimensional unwrapped image. Then, a series of image processes is used to normalise, segment and detect the defects. Freedom of orientation is one of the advantages of the system, since it permits users to place a to-be-inspected lens holder on the fixture at an arbitrary orientation. Furthermore, a novel global image restoration scheme, based on randomised singular value decomposition, is proposed in this study, in order to quickly detect defects embedded in the high-resolution surface.